2016
DOI: 10.1093/ntr/ntw148
|View full text |Cite
|
Sign up to set email alerts
|

Is the Effect of Anhedonia on Smoking Cessation Greater for Women Versus Men?

Abstract: Introduction: Anhedonia has been recognized as a major risk factor for smoking persistence. Potential gender differences in the effect of anhedonia on smoking cessation have not been studied. Using data from a completed clinical trial of maintenance nicotine patch therapy, we hypothesized that gender would moderate the effect of anhedonia on short-term abstinence, such that anhedonic women would be less likely to achieve abstinence. Methods: Participants (N = 525; 50% female, 48.2% Black/African American, aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 25 publications
1
7
1
Order By: Relevance
“…The present findings, along with those of prior studies that show either no relationship between low PA and quitting (Schnoll et al, 2013) or a positive relationship between anhedonia and quitting (Powers et al, 2016), suggest caution regarding the proposal that increased PA should be a central focus of targeted treatments in order to improve cessation outcomes (Audrain-McGovern, Wileyto, Ashare, Cuevas, & Strasser, 2014; Hoeppner, Hoeppner, Kelly, Schick, & Kelly, 2017; Leventhal et al, 2014; Leventhal et al, 2008). At the same time, the results of three pilot studies do suggest some early potential for interventions that focus primarily on boosting PA to assist smokers with low PA to quit successfully (Kahler et al, 2014; Kahler et al, 2015; MacPherson et al, 2010).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…The present findings, along with those of prior studies that show either no relationship between low PA and quitting (Schnoll et al, 2013) or a positive relationship between anhedonia and quitting (Powers et al, 2016), suggest caution regarding the proposal that increased PA should be a central focus of targeted treatments in order to improve cessation outcomes (Audrain-McGovern, Wileyto, Ashare, Cuevas, & Strasser, 2014; Hoeppner, Hoeppner, Kelly, Schick, & Kelly, 2017; Leventhal et al, 2014; Leventhal et al, 2008). At the same time, the results of three pilot studies do suggest some early potential for interventions that focus primarily on boosting PA to assist smokers with low PA to quit successfully (Kahler et al, 2014; Kahler et al, 2015; MacPherson et al, 2010).…”
Section: Discussioncontrasting
confidence: 62%
“…Cook, Spring, McChargue, & Doran, 2010) smokers, or (b) smokers receiving antidepressant pharmacotherapy (Doran et al, 2006), limiting generalizability. Recent studies that do not have these characteristics have been more mixed, with some studies supporting the relationship between low PA or anhedonia and smoking cessation (Castro et al, 2014; Leventhal et al, 2014) and others failing to demonstrate a relationship (Schnoll, Leone, & Hitsman, 2013) or showing that anhedonia predicted better cessation outcomes (Powers et al, 2016). Consequently, additional evaluation of the predictive value of PA or smoking cessation is warranted, including a replication of the finding that low PA offers unique predictive value beyond the broader construct of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Only in one study did anhedonia have a positive effect on treatment (30). In the clinical cessation trial on 21-mg nicotine patch a day for 8 weeks, 70 participants were anhedonic based on the SHAPS.…”
Section: Resultsmentioning
confidence: 99%
“…Of interest in this review is the finding that substitution treatment (i.e., nicotine patch) might be beneficial specifically for smokers scoring high on anhedonia. Powers et al (30) showed an increased likelihood of short-term abstinence using a 21-mg/day nicotine patch therapy. Cook et al (34) observed that administering nicotine replacement therapy suppressed abstinence-induced anhedonia and alleviated nicotine withdrawal symptoms during short-term abstinence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation